The Effect of Work-Life Balance on Turnover Intention Mediated by Burnout - Raniasari Bimanti Esthi; Saur Panjaitan (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2023)
The sales Officer (SO) is a banking employee in the lending section. To achieve the monthly target SO is willing to work overtime. This causes an unbalanced work life and makes employees very tired, then start thinking about changing jobs. The purpose of this study was to (1) determine the effect of work-life balance on turnover intention, (2) determine the effect of work-life balance on burnout, (3) determine the effect of burnout on turnover intention, and (4) determine the effect of work-life balance on turnover intention mediated by burnout. The population in this study were all banking employees in Indonesia who work in sales in the lending department. Sampling was carried out using a non-probability technique, namely convenience sampling. Data were analyzed using the PLS approach SEM method. Based on the research results, there are findings that WLB has no effect & is not significant on TI. WLB influences burnout, burnout influences IT, and WLB affects TI through burnout.